Similarities and differences in teaching behavior for honors and regular bachelor’s education - Tineke Kingma; Anneke Smits; Marjolein Heijne-Penninga; Debbie Jaarsma; Joke Voogt (Journal of the European Honors Council, 2024)
Many institutions of higher education offer honors education, but research on teacher behavior in honors classes is scarce. Our aim is to gain deeper understanding of how teachers adapt their teaching practices in the honors classroom as compared with the regular classroom. We conducted semi-structured interviews with 12 Dutch teachers who teach in both types of classroom. Using self-determination theory as an analytical framework, we found that teachers supported the basic psychological needs of autonomy, competence, and relatedness in both settings in order to promote intrinsic motivation. However, there were differences in how and why these behaviors were enacted. Teachers had different ways of expressing basic psychological needs. In the regular classroom, the main focus of the teachers is on preparing students to become autonomous professionals, whereas in the honors classroom, the main focus is on personal development and individual learning.